Abnormal Wear due to Synergistic Effects of Corrosion and Cavitation in High-Speed Flow of Glycol-Based Hydraulic Fluid Valve Surfaces - Ryota Takasaka; Noritsugu Umehara; Takayuki Tokoroyama; Ruixi Zhang; Koichi Okamura; Junichi Fukuda; Tetsuya Hayashi; Kohei Abe; Satoshi Wakamatsu (Tribology Online, 2025)
Hydraulic control systems, known for their efficiency and high responsiveness, are widely used in industries such as aerospace, automotive, and construction. Recent advancements have integrated mechatronics and intelligent systems into traditional hydraulics, improving precision and functionality. However, challenges such as cavitation erosion in hydraulic valves remain critical, especially in automotive linear solenoid valves. Cavitation occurs when liquid pressure drops below its vapor pressure, forming bubbles that collapse violently, causing erosion and potentially degrading valve performance. This study examines the impact of glycol-based hydraulic fluids on cavitation erosion. Observation of the wear surface and elemental analysis revealed that the synergistic effects of the corrosive action of the hydraulic fluid and the impact pressure of cavitation caused severe valve wear in the experiment using Fluid A. Experiments with different base oils and additives for the hydraulic fluid suggested the types of additives that promote corrosion and the methods and mechanisms used to inhibit corrosion.